Pornografi dan Pornoaksi: Perspektif Agama dan Kesehatan Mental - Syamsu Syauqani (Universitas Islam Negeri Mataram, 2006)
Discussing about pornography and erotic actions is mostly about the debate among religious defenders, cultural practitioners and activists of human rights. This is due to the fact that the three parties have their own point of views in perceiving the constitution of pornography and erotic actions. They have different perception especially from religion’s point of view. This writing—with no intention to interfere the debate—tries to understand pornography and erotic actions from religion and mental health. Religion in this context is not meant as the complicated or liberal term but rather on the normative-theological doctrine which intents to give both physical and mental healthy life. Islam claims to have a teaching which leads to mental health by forbidding immoral deeds such as pornography and erotic actions. Therefore, to support the religion perception on pornography and erotic actions, this writing reveals that pornography and erotic actions as ‘mental sickness’.